Magnetic Resonance Imaging of the Codman Microsensor Transducer Used for Intraspinal Pressure Monitoring: Findings From the Injured Spinal Cord Pressure Evaluation Study. Issue 10 (May 2016) - Phang, Isaac; Mada, Marius; Kolias, Angelos G.; Newcombe, Virginia F. J.; Trivedi, Rikin A.; Carpenter, Adrian; Hawkes, Rob C.; Papadopoulos, Marios C.
Abstract : Study Design: Laboratory and human study. Objective: To test the Codman Microsensor Transducer (CMT) in a cervical gel phantom. To test the CMT inserted to monitor intraspinal pressure in a patient with spinal cord injury. Summary of Background Data: We recently introduced the technique of intraspinal pressure monitoring using the CMT to guide management of traumatic spinal cord injury [Werndle et al. Crit Care Med 2014;42:646]. This is analogous to intracranial pressure monitoring to guide management of patients with traumatic brain injury. It is unclear whether magnetic resonance imaging (MRI) of patients with spinal cord injury is safe with the intraspinal pressure CMT in situ . Methods: We measured the heating produced by the CMT placed in a gel phantom in various configurations. A 3-T MRI system was used with the body transmit coil and the spine array receive coil. A CMT was then inserted subdurally at the injury site in a patient who had traumatic spinal cord injury and MRI was performed at 1.5 T. Results: In the gel phantom, heating of up to 5°C occurred with the transducer wire placed straight through the magnet bore. The heating was abolished when the CMT wire was coiled and passed away from the bore. We then tested the CMT in a patient with an American Spinal Injuries Association grade C cervical cord injury. The CMT wire was placed in the configuration that abolished heating in the gel phantom. Good-quality T1 and T2 images of the cord were obtained without neurological deterioration. The transducer remained functional after the MRI. Conclusion: Our data suggest that the CMT is MR conditional when used in the spinal configuration in humans. Data from a large patient group are required to confirm these findings. Level of Evidence : N/A